TINGKAT KEPUASAN GURU TERHADAP KURIKULUM 2013 - Mustaqim, Mujahidil (Prodi Teknologi Pendidikan, 2019)
This article is based on the issuance of regulations that state that there is a revision of the 2013 curriculum. This new regulation is the answer given by the government for the chaos that occurred at the beginning of the 2013 curriculum. The noise of the 2013 curriculum was illustrated by the absence of curriculum trials, then there was also no socialization and teacher training on how to implement the new curriculum as well as changes in content, approach and evaluation which are considered quite complicated than before. The government considers the 2013 curriculum changes to be better than the previous curriculum and in accordance with the conditions of need in the field. However, this is not the case with education practitioners and curriculum implementers in the field who consider that the 2013 curriculum has many technical problems and is very burdensome for teachers. In 2016, a new government regulation was officially issued to resolve the problems that arise. With the arrival of this new regulation, a quantitative study was conducted on teachers regarding the level of teacher satisfaction with the 2013 curriculum revision. The results of the study stated that 90.85% of teachers expressed satisfaction and agreed with the presence of the 2013 curriculum revision. The level of satisfaction was seen from three of the four existing improvements. in the 2013 curriculum revision, namely, First, as many as 78.27% of teachers are satisfied with the effort to restructure spiritual and social attitude competencies in all subjects. Second, as many as 94.29% of subject teachers agreed with the KI-KD coherence and document alignment. Third, the dominance of teachers expresses their satisfaction with providing creative space for teachers in implementing the curriculum in the 2013 curriculum revision regulation.Artikel ini didasari atas terbitnya regulasi yang menyatakan adanya revisi kurikulum 2013. Regulasi baru ini merupakan jawaban yang diberikan pemerintah atas carut marut yang terjadi pada awal kehadiran kurikulum 2013. Kegaduhan kehadiran kurikulum 2013 tergambar dari tidak adanya ujicoba kurikulum, kemudian berlanjut juga tidak ada sosialisasi dan pelatihan guru terhadap how to implementasikan kurikulum baru serta perubahan isi, pendekatan dan evaluasi yang dinilai cukup rumit dari sebelumnya. Pemerintah menganggap secara subtansi kurikulum 2013 perubahan lebih baik dari kurikulum sebelumnya dan sesuai dengan kondisi kebutuhan di lapangan. Namun tidak demikian halnya dengan praktisi pendidikan dan implementator kurikulum di lapangan yang menilai bahwa kurikulum 2013 banyak mengalami kendala secara teknis dan sangat memberatkan guru. Tahun 2016, secara resmi keluar peraturan pemerintah baru guna menyelesaikan persoalan yang timbul. Dengan datangnya regulasi baru ini, dilakukan penelitian kuantitatif kepada guru tentang tingkat kepuasan guru terhadap revisi kurikulum 2013. Hasil penelitian menyebutkan bahwa 90,85 % guru menyatakan puas dan setuju dengan kehadiran revisi kurikulum 2013. Tingkat kepuasaan dilihat dari tiga dari empat pokok perbaikan yang ada dalam revisi kurikulum 2013, yakni, Pertama, sebanyak 78,27 % guru puas dengan upaya penataan kembali kompetensi sikap spiritual dan sosial pada semua mata pelajaran. Kedua, sebanyak 94,29 % guru mata pelajaran menyatakan setuju dengan koherensi KI-KD dan penyelarasan dokumen. Ketiga, dominasi guru mengungkapkan kepuasan mereka dengan pemberian ruang kreatif kepada guru dalam mengimplementasikan kurikulum dalam regulasi revisi kurikulum 2013.